ARCHEAN ZIRCONS FROM THE MANTLE: THE JORMUA OPHIOLITE REVISITED - Peltonen P.; Manttari I.; Huhma H.; Kontinen A. (My University, 2003)
The Jormua ophiolite represents seafloor from an Early Proterozoic ocean to continent transition zone that mainly consisted of Archean subcontinental lithospheric mantle. These mantle rocks were exhumed as a result of extreme crustal thinning and detachment faulting in association with the opening of the Svecofennian Sea. At the prerift stage of continental breakup, residual lithospheric peridotites became intruded by alkaline melts that formed a diverse suite of clinopyroxenite and hornblendite-garnetite dikes and veins. These Proterozoic dikes contain Archean zircon xenocrysts inherited from deeper sources of the continental mantle. The relatively large spread of 207Pb/206Pb ages between 3106 and 2718 Ma suggests that the zircons are derived from a variety of source rocks. Some xenocrysts have U and Th abundances comparable to zircon in common alkali basalts, whereas a population of Archean high-U and high-Th zircons is similar to those described from mica-amphibole-rutile-ilmenite-diopside-bearing mantle xenoliths. These are the oldest zircons found from upper-mantle rocks anywhere and imply that the Fennoscandian cratonic root was relatively cool and strongly metasomatized by ca. 3.1 Ga. [PUBLICATION ABSTRACT]
Keywords: zircon; mantle origin; ophiolite; rifting; Fennoscandian Shield; Finland; Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Архей; Precambrian::Archean; Докембрий::Протерозой